UJI EFEKTIVITAS PUPUK DAUN PADA BEBERAPA ARAS PEMBERIAN GUANO TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) - Mohamad Ihsan Tri Pamujiasih (AGRONOMIKA, 2012)
The objective of the research was to know the effective application of foliar fertilizer and several level of guano on growth and yield of tomato plant. This pot experiment was conducted in the glass house which arranged as factorial Completely Randomized Design with two factors as treatment that were: concentration of foliar fertilizer i.e. : 0,5 cc/ lt of water, 1 cc/lt of water and 1,5 cc/ lt of water and the second factor was application of guano that were three levels: guano 200 kg/ha of guano, 275 kg/ha of guano and 350 kg/ha of guano. The tomato planted and there were several parameters of plant growth and yield were observed. Result of research showed that there were significant relation between the concentration of foliar fertilizer and guano application toward all parameters of plant growth and yield observed. Can be concluded that there was an effective influence of foliar fertilization on plant growth and yield and the best concentration of foliar fertilizer was 1,5 cc/lt of water which combine with application 350 kg/ha of guano.